Independent Predictors of Time to Relapse after CIS in High-Risk Patients - Spelman, T.; Meyniel, C.; Trojano, M.; Lugaresi, A.; Izquierdo, G.; Grand'Maison, F.; Butzkueven, H. (Sage Publications Ltd, 2014)
…
Joint ACTRIMS-ECTRIMS Meeting -- SEP 10-13, 2014 -- Boston, MA